Modeling the thermal dynamics of the active layer at two contrasting permafrost sites on Svalbard and on the Tibetan Plateau - Weismüller, Jens; Wollschläger, Ute; Boike, Julia; Pan, Xicai; Yu, Q.; Roth, Kurt (The Cryosphere, 2011)
Abstract. Employing a one-dimensional, coupled thermal and hydraulic numerical model, we quantitatively analyze high-resolution, multi-year data from the active layers at two contrasting permafrost sites. The model implements heat conduction with the de Vries parameterization, heat convection with water and vapor flow, freeze-thaw transition parameterized with a heuristic soil-freezing characteristic, and liquid water flow with the Mualem-van Genuchten parameterization. The model is driven by measured temperatures and water contents at the upper and lower boundary with all required material properties deduced from the measured data. The aims are (i) to ascertain the applicability of such a rather simple model, (ii) to quantify the dominating processes, and (iii) to discuss possible causes of remaining deviations. Soil temperatures and water contents as well as characteristic quantities like thaw depth and duration of the isothermal plateau could be reproduced. Heat conduction is found to be the dominant process by far at both sites, with non-conductive transport contributing a maximum of some 3% to the mean heat flux at the Spitsbergen site, most of the time very much less, and practically negligible at the Tibetan site. Hypotheses discussed to explain the remaining deviations between measured and simulated state variables include, besides some technical issues, infiltration of snow melt, dry cracking with associated vapor condensation, and mechanical soil expansion in detail.
Gesehen am 16.11.2022